THE ASSESSMENT CRITERIA OF MANAGER’S PERSONAL QUALITIES IN THE TRANSFORMATIONAL SOCIETY - Stepanyan , A.A. (Modern Psychology, 2019)
The approaches about manager’s personal qualities in modern society are discussed in the article. The article discusses various scientific approaches to the personal qualities of leaders in modern society. The aim of our study was to determine the criteria for a successful leader, which will be relevant and practical in our society. 419 As part of the study, an expert survey was carried out, which was carried out using the questionnaire we compiled to determine the important personal qualities of the leader. The results of the study will evaluate successful leaders to determine patterns in the process of professional development.
Keywords: manager, professional development, successful specialist, transformational society.